Single-domain antibody delivery using an mRNA platform protects against lethal doses of botulinum neurotoxin A - Panova, Eugenia A.; Kleymenov, Denis A.; Shcheblyakov, Dmitry V.; Bykonia, Evgeniia N.; Mazunina, Elena P.; Dzharullaeva, Alina S.; Zolotar, Anastasia N.; Derkaev, Artem A.; Esmagambetov, Ilias B.; Sorokin, Ivan I.; Usachev, Evgeny V.; Noskov, Anatoly N.; et al. (Frontiers in Immunology, 2023)
Single-domain antibodies (sdAbs, VHHs, or nanobodies) are a promising tool for the treatment of both infectious and somatic diseases. Their small size greatly simplifies any genetic engineering manipulations. Such antibodies have the ability to bind hard-to-reach antigenic epitopes through long parts of the variable chains, the third complementarity-determining regions (CDR3s). VHH fusion with the canonical immunoglobulin Fc fragment allows the Fc-fusion single-domain antibodies (VHH-Fc) to significantly increase their neutralizing activity and serum half-life. Previously we have developed and characterized VHH-Fc specific to botulinum neurotoxin A (BoNT/A), that showed a 1000-fold higher protective activity than monomeric form when challenged with five times the lethal dose (5 LD50) of BoNT/A. During the COVID-19 pandemic, mRNA vaccines based on lipid nanoparticles (LNP) as a delivery system have become an important translational technology that has significantly accelerated the clinical introduction of mRNA platforms. We have developed an mRNA platform that provides long-term expression after both intramuscular and intravenous application. The platform has been extensively characterized using firefly luciferase (Fluc) as a reporter. An intramuscular administration of LNP-mRNA encoding VHH-Fc antibody made it possible to achieve its rapid expression in mice and resulted in 100% protection when challenged with up to 100 LD50 of BoNT/A. The presented approach for the delivery of sdAbs using mRNA technology greatly simplifies drug development for antibody therapy and can be used for emergency prophylaxis.